2004
DOI: 10.1345/aph.1d113
|View full text |Cite
|
Sign up to set email alerts
|

Use of β-Blockers in Patients with COPD

Abstract: The literature supports the safety and mortality benefits of using beta-blockers in COPD. Patients with mild to moderate COPD should receive cardioselective beta-blocker therapy when a strong indication exists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…Several meta-analyses concluded that cardioselective β-blockers do not produce clinically significant adverse respiratory effects in patients with chronic obstructive pulmonary disease, suggesting that β-blockers should not be withheld from these patients. 196,197 …”
Section: β-Blockersmentioning
confidence: 99%
“…Several meta-analyses concluded that cardioselective β-blockers do not produce clinically significant adverse respiratory effects in patients with chronic obstructive pulmonary disease, suggesting that β-blockers should not be withheld from these patients. 196,197 …”
Section: β-Blockersmentioning
confidence: 99%
“…Two recent meta-analyses concluded that cardioselective ␤-blockers do not produce clinically significant adverse respiratory effects in patients with mild to moderate reactive airway disease, 110,111 which suggests that ␤-blockers should not be withheld from these patients.…”
Section: ␤-Blockersmentioning
confidence: 99%
“…Criteria from the adjusted Beers list, McLeod's list, and Lindblad's list of clinically important drug-disease interactions are combined and respective data updated [10][11][12][61][62][63][64][65][66][67][68][69]. Some of the inappropriate drugdisease combinations are defined by all three tools, such as NSAIDs in peptic ulcer disease or tricyclic antidepressant in benign prostate hyperplasia.…”
Section: The New Comprehensive Protocolmentioning
confidence: 99%